Stigma, lack of knowledge and prevalence maintain HIV risk among Black Africans in New Zealand. (5th January 2015) - Henrickson, Mark; Dickson, Nigel; Mhlanga, Fungai; Ludlam, Adrian
Abstract: Objective: The AfricaNZ Health project aimed explore HIV risks in Black African communities in NZ with a view to informing HIV infection prevention and health promotion programs. Methods: AfricaNZ Health was completed in two phases. The first developed desk estimates of the resident Black African population in New Zealand, and Africans living with HIV. The second comprised two arms: an anonymous survey administered at African community events and a series of focus groups around the country. Results: High levels of knowledge and positive attitudes about HIV were more often found in older than younger age groups. Condom use was higher in the younger group than in older age groups. Traditional attitudes still inform some beliefs about HIV. Stigma about HIV and anyone at risk for HIV remains very high among Africans. Western sexual identity constructs are not meaningful. Conclusions: A culturally informed strategy for risk and stigma reduction is urgently needed. Implications: The existing prevention and care infrastructure, informed by MSM experiences, must address increased risk to Black African new settlers, but this is not a reason to discriminate or further stigmatise an already vulnerable population.